"We’re vulnerable too": an (alternative) analysis of vulnerability within criminal legal aid and police custody - Dehaghani, Roxanna (Oñati Socio-Legal Series, 2017)
This paper considers criminal justice through the lens of vulnerability theory, drawing attention to unexplored or underexplored vulnerabilities in the criminal justice system of England and Wales. We address three layers of vulnerability. The first identifies those who have more traditionally, although not unproblematically, attracted the label ‘vulnerable’; suspects in the criminal process. The second examines the vulnerability of those who, as humans, can be appreciated as vulnerable, but, within their roles in the criminal process, are not typically considered vulnerable - custody officers and defence lawyers. The third, least considered, explores the vulnerability of institutions - the police service and criminal legal aid system. Institutional failure to provide resources, and thus bolster the resilience of suspects and practitioners, can serve to further exacerbate vulnerability. Using empirical data, we explore how vulnerability manifests within the crucial early stages of the criminal process. In doing so, we provide a more holistic and critical account of vulnerability within the criminal justice system.